Alternative carbon feedstock for the chemical industry? - Assessing the challenges posed by the human dimension in the carbon transition. (10th May 2019) - Lee, Roh Pin
Abstract: Our society faces a carbon dilemma whereby there is an imbalance between our need for carbon and the dark side of its utilization. Unlike electricity, heat and mobility sectors where a transition towards renewable energy sources is possible, the chemical industry has no alternative to carbon sources for its production. This paper carried out a case analysis of the German chemical industry. The objective is to identify challenges posed by the human dimension for its carbon transition from a dependence on imported carbon resources towards cleaner and sustainable production using domestic primary and secondary carbon feedstock alternatives. Findings from a representative survey study carried out in Germany in October 2017 showed widespread public misconceptions regarding what are carbon sources and a lack of mental associations regarding the use of domestic biomass, coal, waste and CO2 as feedstock alternatives for chemical production. Furthermore, significant regional difference in support/resistance for coal-to-chemicals as a carbon transition route is also observed. This paper represents a first effort to bridge the gap between transition and circular economy research to facilitate the early identification of human-related barriers to a carbon transition for the chemical industry. Highlights: A carbon transition for the chemical industry from a dependence on imported carbon resources to using domestic carbon feedstock alternatives. Case analysis of the German chemical industry. Overview of biomass, coal, waste and CO2 as domestic chemical feedstock alternatives and policy drivers and obstacles for different options. Public awareness, perception and acceptance of domestic carbon resources as feedstock alternatives for the chemical industry. Early identification of human-related barriers to a carbon transition for the chemical industry.